An evolutionary programming approach to solve price-based unit commitment (PBUC) problem in electricity market / Barbara Minot Thomas - Thomas, Barbara Minot (2017)
This study presents an evolutionary programming method to solve profit based unit commitment (PBUC) problem by considering the power and reserve energy. PBUC problem is a mixed integer and continuous nonlinear optimization problem. PBUC is difficult to solve due to the tremendous dimension, the objective function is non-linear, and it involves a lot of constraints. In this study, PBUC is used to maximize profit while satisfying the forecasted demand and constraints. Evolutionary Programming (EP) is used in this study to solve PBUC problem while considering market rule. The proposed method is tested on a three generation units system and the results show that this method is able to provide the solution to PBUC problem.